Tetra-3-[(2-diethylamino)ethyl]-7-oxo-4-methylcoumarin-substituted zinc phthalocyanines: Synthesis, characterization and aggregation effects on photophysical/photochemical properties - (:unkn) unknown (ELSEVIER SCIENCE SA, 2010)
A synthesis of a novel zinc phthalocyanine with four 3-[(2-diethylamino)ethyl]-7-oxo-4-methylcoumarin dye groups at the non-peripheral positions was performed and characterized. The photophysical and photochemical properties of the peripherally (p) and non-peripherally (np) tetra-3[(2-diethylamino)ethyl]-7-oxo-4-methylcoumarin substituted zinc (II) phthalocyanines are reported. The effects of the position of the substituents and the aggregation on the photophysical/photochemical properties of these complexes are also investigated. General trends are described for photodegredation, singlet oxygen and fluorescence quantum yields, and fluorescence lifetimes in dimethylsulphoxide (DMSO) for np-ZnPc and in both DMSO and DMSO+Triton-X 100 solutions for p-ZnPc. The fluorescence of the tetra-substituted zinc phthalocyanine complexes (np-ZnPc and p-ZnPc) are effectively quenched addition of 1,4-benzoquinone (BQ). (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Coumarin (2H-chromen-2-one); Fluorescence; Phthalocyanine; Quantum yield; Singlet oxygen; Zinc; PHOTOCHEMICAL PROPERTIES; PHOTOPHYSICAL PROPERTIES; PECHMANN REACTION; QUANTUM YIELDS; PHOTOSENSITIZERS; SUBSTITUENTS; DERIVATIVES; SEPARATION; COMPLEXES; COUMARINS